Expressive Illocutionary Act in the Little Mermaid 1989 Movie - Ni Kadek Dian Trisnawati; Desak Putu Eka Pratiwi; I Putu Andri Permana (e-Journal of Linguistics, 2023)
This article discusses about expressive illocutionary act in The LittleMermaid 1989 Movie. This article analyzing the data used descriptivequalitative method. The aims of this article are to identify the types ofexpressive illocutionary act and the context of situation in the movie.This article used theory by Searle (1979) to identify the types ofexpressive illocutionary act and theory by Halliday and Hasan (1985)to analyze the context of situation. The result of this article showed 22utterances which are produced by the characters.